Analisis Upaya Sekuritisasi Isu Nelayan Migran Oleh Pemerintah Indonesia Berdasarkan Ktt Asean ke-42 - Rosalia, Chaterine (PT. Publikasiku Academic Solution, 2025)
The 42nd ASEAN Summit, which took place on May 23, 2023, resulted in the agreement of the ASEAN Declaration on The Placement and Protection of Migrant Fishers. The declaration is complementary to complement the existing framework considering that so far the issue of migrant fishers has not been specifically discussed in ASEAN forums and only focuses on the issue of worker employment on the mainland and has not answered the issue of migrant fishermen. This research focuses on how Indonesia responds to the ASEAN Declaration on The Placement and Protection of Migrant Fishers in an effort to protect migrant fishermen. It is estimated that there are 1.2 million migrant workers working as crew members, 35,000 of whom work on commercial fishing vessels. The problems faced by Indonesian crew members are generally related to unreasonable working conditions, persecution, work accidents, salary delays, as well as recruitment schemes and long employment contract bureaucracy. With these problems, this research will be studied through the concept of national interests and international organizations. The method that will be used in this research is descriptive. The research was carried out through literature studies and data processing through existing records. The results of this research are to find out what efforts have been made by the Indonesian government to ensure the safety of Indonesian Migrant Workers.